Nexus between monetary policy shock and financial imbalance in India - Kumar, Kundan; Paramanik, Rajendra Narayan; Ansari, Zeeshan Nezami (Asian Journal of Economic Modelling, 2023)
During the 1990s and early 2000s, it was a widely adopted global practice to utilize interest rates as a means to stabilize inflation and output, with the aim of addressing financial imbalances. However, the Global Financial Crisis and the recent pandemic challenged this consensus, leading to a heated debate over the appropriate role of monetary policy. This motivated us to hypothesis the nexus between monetary policy shocks and financial imbalances against the backdrop of economic policy uncertainty (EPU) in India. We have used the principal component analysis method to construct a financial index using critical financial variables. The index is further used to derive financial imbalances. The relation between financial imbalance and monetary policy shock is found to be negative and statistically significant during 2008-2012, generally marked as a period of high EPU caused by the great depression of 2008. Afterwards, the phase of moderation persists until 2019 and the arrival of recent pandemic. However, during the pandemic, the EPU has escalated and strengthened the positive relationship between financial imbalance and monetary policy. Overall, the findings of this study indicate that EPU plays a significant role in the interplay between monetary policy and financial imbalance. In terms of policy implications, our findings suggest that monetary policy is ineffective in preserving financial stability during periods of high uncertainty, and hence policymakers should focus on alternative measures.